Acute obinutuzumab-induced thrombocytopenia in follicular lymphoma: case report and literature review - Zhou, Jieyi; Chen, Miaomiao; Zhang, Yi; Xu, Ce; Li, Rong (Frontiers in Oncology, 2025)
IntroductionObinutuzumab, a type II anti-CD20 monoclonal antibody used in the treatment of follicular lymphoma, is associated with a higher incidence of adverse events, including thrombocytopenia, compared to rituximab. We report a case of severe, acute thrombocytopenia induced by obinutuzumab and explore its potential mechanism.Case presentationA 47-year-old woman with follicular lymphoma developed recurrent, severe (grade III–IV) thrombocytopenia within 24 h following obinutuzumab administration, starting from her second treatment cycle. Subsequent bone marrow aspiration revealed significant megakaryocyte hyperplasia but with impaired platelet production. Key laboratory findings included elevated levels of pro-inflammatory cytokines TNF-α and IL-6, decreased complement levels, and reduced IgM, while the platelet antibodies tested were negative. The patient’s thrombocytopenia was managed and improved with treatments including recombinant human thrombopoietin (rhTPO) and platelet transfusions.ConclusionObinutuzumab can rarely cause acute, severe thrombocytopenia, possibly through a combination of immune-mediated platelet destruction and impaired megakaryocyte maturation.